Digital Marketing Strategy As A Catalyst For SME Growth In The Modern Era - Made Setini; I Made Suniastha Amerta; Ni Luh Putu Indiani; Putu Ayu Sita Laksmi; Evi Triandini; Aris Puji Purwatiningsih; Gede Suardana (UNIVED Press, 2025)
This study aims to explore the influence of digital marketing strategies on the performance of Small and Medium Enterprises (SMEs) in Bali. Through a quantitative approach, this study tests the hypothesis that various digital marketing strategies-including search engine optimisation, content marketing, social media marketing, email marketing, and influencer marketing-significantly predict SME performance. The findings show that the implementation of these strategies contributes to increased sales, market share, and better customer relationships. Although the hypothesis regarding dynamic environment moderation did not show significant effects, the study identified challenges that SMEs face, such as resource limitations and digital literacy deficits. The results recommend that SMEs should utilise digital channels more effectively and conduct data-driven analysis to optimise marketing strategies. This research confirms the importance of digital marketing as a vital tool for the growth and success of SMEs in Bali.